Akar-akar Kanan daripada Nasionalisme Indonesia: Nasionalisme Jawa dalam Konteks Kesejarahannya - Farabi Fakih (Universitas Gadjah Mada, 2014)
This papers explores the thoughts of Javanese nationalists during the early phase of Indonesian nationalism. It will specifcally look into the ideas of Tjipto Mangoenkoesoemo and Noto Soeroto as prototypes of new nationalist sentiments that grew during a period of intense revolutionary fervor, marked by the rise of marxism and fascism throughout the world. By looking at these factors, it wants to situate the global roots of Indonesian nationalism and contextualize Indonesian nationalist history within the global development of the early twentieth century.